Gender differences in marathon pacing and performance prediction - Hubble, C.; Zhao, J. (Journal of Sports Analytics, 2016)
In this study, we demonstrate that men overestimate their marathon abilities compared to women and propose that this may result from men`s relative overconfidence as well as lead men to execute suboptimal race strategy relative to women. We present a novel dataset of marathoners` predicted finish times from the 2013 Houston Marathon. Using the runners ex-ante predictions of their own marathon finish times, we show that men consistently overestimate their abilities relative to women. Further, we find that men slow more than women in the later stages of the race and find that less even pacing is correlated with worse marathon performance, results in-line with previous studies. Finally, we argue that this poor pacing is in part explained by men`s overconfidence.